Dirac semimetals Tamm plasmons-induced low-threshold optical bistability at terahertz frequencies - Huayue Zhang; Xin Long; Hongxia Yuan; Xiaoyu Dai; Zhongfu Li; Leyong Jiang; Yuanjiang Xiang (Results in Physics, 2022)
In this paper, we theoretically study the optical bistability (OB) of reflected beams in a composite multilayer structure with three-dimensional Dirac semimetals (3D DSMs) and one-dimensional photonic crystal (1D PC) on both sides of the spacer layer. The optical Tamm states (OTSs) excited by the 3D DSMs-1D PC multilayer structure significantly enhances the local electric field near the nonlinear 3D DSMs, which provides a positive condition for the realization of low threshold OB. Through parameter optimization, we obtain a threshold electric field with an incident electric field of 106 V/m levels. Furthermore, the influences of the Fermi energy of 3D DSMs, the angle of the incident light and dispersion characteristics of the spacer layer on the hysteretic behavior and the threshold of OB are clarified. We believe above results will provide possible options for nonlinear optical bistable devices.